Urban-Rural Differentiation in Serbia Beyond the Women’s Role in the Local Labor Force - Drobnjaković Marija; Panić Milena (European Countryside)
Differentiation between rural and urban areas in Serbia is a disputable issue, usually based on the most commonly used indicators which do not reflect the functional and social local features. This research starts from the hypothesis that labor market gender inequality is strongly correlated with urban-rural dichotomy and patriarchal patterns on women's position. It follows the hidden idea of rural life in Serbia beyond the social and economic local features, introducing a gender dimension as a significant element. The cluster analysis is performed, which involves ten variables that represent the differences in women's social and economic engagement. Results enabled the identification of five municipality clusters, whose interpretation illustrated women's current position and significance in shaping (under)developed municipalities and urban/rural societies.